ANALISIS KEPUASAN PENGGUNA TERHADAP APLIKASI MOBILE LAYANAN TELEKOMUNIKASI BIMAPLUS MENGGUNAKAN METODE EUCS - Fadillah, Muhammad Rezky; Megawati; Saputra, Eki; Rozanda, Nesdi Evrylian (The Indonesian Journal of Computer Science, 2025)
The Bima Plus application, launched by the Tri Provider, was the subject of a study aimed at analyzing the factors influencing user satisfaction. The End User Computing Satisfaction (EUCS) model was employed for this research. Seven variables were identified as influencing user satisfaction: Ease of Use (EOU), Timeliness (TIM), Security (SEC), Speed of Response (SOR), Content (CON), Accuracy (ACC), and Format (FOR). Analysis results indicated that four variables—Ease of Use, Timeliness, Security, and Speed of Response—had a significant impact on user satisfaction, with Security being the most dominant factor (coefficient of 0.497). Conversely, Content, Accuracy, and Format did not demonstrate significant influence. These findings suggest that security is the primary factor influencing user satisfaction, followed by response speed, timeliness, and ease of use.